Reforming the Legal Framework of Ukraine's Economic System: Challenges, Governance, and Regulatory Transformation - Yevhen Leheza (Journal of Nusantara Economy, 2026)
This study examines the reform of Ukraine’s tax law framework as a strategic component of economic modernization in the context of European integration, digital governance, and post-war reconstruction. It aims to evaluate the extent to which existing legal and institutional arrangements support regulatory effectiveness, legal certainty, fiscal sustainability, and financial security while aligning national tax legislation with European Union standards, OECD principles, and international regulatory frameworks. The research employs a qualitative field research design using semi-structured interviews with government officials, tax administrators, legal practitioners, business representatives, and academic experts. Data collection is complemented by direct observation and documentary analysis of tax legislation, administrative regulations, judicial decisions, strategic policy documents, and official institutional reports. Data are analyzed through thematic analysis, supported by statutory interpretation, comparative legal analysis, and source triangulation to ensure analytical validity, consistency, and credibility. The findings indicate that Ukraine’s tax regulatory system continues to face substantial structural challenges, including legislative instability, fragmented institutional coordination, administrative inefficiency, limited accountability, and partial inconsistencies with European Union legal standards. Nevertheless, the study demonstrates significant progress through the digital transformation of tax administration, procedural simplification, greater regulatory transparency, improved taxpayer services, and gradual harmonization with European Commission recommendations and OECD tax governance principles. The analysis further reveals that sustainable tax reform requires an integrated governance model founded on legal certainty, adaptive legislation, digital public administration, risk-based tax supervision, institutional resilience, and collaborative governance involving public authorities, private stakeholders, and international partners. The study contributes to comparative economic law by developing an integrated legal framework that connects tax law reform, digital governance, fiscal security, and European regulatory convergence as mutually reinforcing pillars of economic modernization. The proposed framework enriches contemporary scholarship on tax governance while offering practical policy guidance for strengthening Ukraine’s legal institutions, enhancing investor confidence, improving fiscal resilience, and supporting sustainable economic recovery within the evolving European legal and economic order.